Increasing the Ascomycin Yield by Relieving the Inhibition of Acetyl/Propionyl-CoA Carboxylase by the Signal Transduction Protein GlnB - Wang, Pan; Wang, Xin; Yin, Ying; He, Mingliang; Tan, Wei; Gao, Wenting; Wen, Jianping (Frontiers in Microbiology, 2021)
Ascomycin (FK520) is a multifunctional antibiotic produced by Streptomyces hygroscopicus var. ascomyceticus. In this study, we demonstrated that the inactivation of GlnB, a signal transduction protein belonging to the PⅡ family, can increase the production of ascomycin by strengthening the supply of the precursors malonyl-CoA and methylmalonyl-CoA, which are produced by acetyl-CoA carboxylase and propionyl-CoA carboxylase, respectively. Bioinformatics analysis showed that Streptomyces hygroscopicus var. ascomyceticus contains two PⅡ family signal transduction proteins, GlnB and GlnK. Protein co-precipitation experiments demonstrated that GlnB protein could bind to the α subunit of acetyl-CoA carboxylase, and this binding could be disassociated by a sufficient concentration of 2-oxoglutarate. Coupled enzyme activity assays further revealed that the interaction between GlnB protein and the α subunit inhibited both the activity of acetyl-CoA carboxylase and propionyl-CoA carboxylase, and this inhibition could be relieved by 2-oxoglutarate in a concentration-dependent manner. Because GlnK protein can act redundantly to maintain metabolic homeostasis under the control of the global nitrogen regulator GlnR, the deletion of GlnB protein enhanced the supply of malonyl-CoA and methylmalonyl-CoA by restoring the activity of acetyl-CoA carboxylase and propionyl-CoA carboxylase, thereby improving the production of ascomycin to 390 ± 10 mg/L. On this basis, the co-overexpression of the β and ε subunits of propionyl-CoA carboxylase further increased the ascomycin yield to 550 ± 20 mg/L, which was 1.9 fold higher than that of the parent strain FS35 (287 ± 9 mg/L). Taken together, this study provides a novel strategy to increase the production of ascomycin, providing a reference for improving the yield of other antibiotics.